1983
DOI: 10.1128/aac.24.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Activities of aztreonam and new cephalosporins against infrequently isolated gram-negative bacilli

Abstract: The susceptibilities of 159 clinical isolates of glucose nonfermentative gramnegative bacilli were determined for eight new monobactam or P-lactam antibiotics. Imipemide (N-formimidoyl thienamycin) was effective against the largest number of species, although not against Pseudomonas maltophilia. Cefoperazone and ceftazidime, but not cefsulodin, were active against infrequently isolated Pseudomonas species. Aztreonam, moxalactam, cefotaxime, and ceftizoxime demonstrated selective activity against several specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…The results of the MIC determinations correlate closely with recent reports (1,4,5,8,12), and similar results with disk diffusion methods were observed (9). Although, we report slightly lower trimethoprim-sulfamethoxazole and tetracycline MICs for 90% of isolates than Kurzynski and associates, the range of MICs is essentially the same (8).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The results of the MIC determinations correlate closely with recent reports (1,4,5,8,12), and similar results with disk diffusion methods were observed (9). Although, we report slightly lower trimethoprim-sulfamethoxazole and tetracycline MICs for 90% of isolates than Kurzynski and associates, the range of MICs is essentially the same (8).…”
supporting
confidence: 80%
“…Infected young turkeys experience oculonasal discharge, tracheal collapse, and decreased weight gains; but mortality is usually low (10). No comprehensive epidemiological studies on the incidence of B. avium infection are available.To date, in vitro antimicrobial susceptibility studies with these two organisms have been conducted with either small numbers of isolates (4) or against panels with limited numbers of antimicrobial agents (1,12 tested against all study isolates at the indicated ranges of concentrations: penicillin, 0.015 to 2.0 ,ug/ml; ampicillin, 0.25 to 16 ,ug/ml; ampicillin-sulbactam, 0.03/0.015 to 16/8 ,ug/ml; ticarcillin, 4 to 64 ,ug/ml; mezlocillin, 2 to 4 ,ug/ml; piperacillin, 1 to 64 ,ug/ml; gentamicin, 1 to 8 ,ug/ml; tobramycin, 1 to 8 ,uglml; amikacin, 2 to 32 ,ug/ml; cephalothin, 1 to 16 ,ug/ml; cefuroxime, 0.5 to 32 ,ug/ml; cefoperazone, 2 to 32 ,ug/ml; ceftazidime, 0.5 to 32 ,ug/ml; cefotaxime, 0.5 to 32 ,ug/ml; ceftriaxone, 0.5 to 32 pug/ml; chloramphenicol, 0.25 to 16 ,ug/ml; erythromycin, 0.12 to 8 ,uglml; rifampin, 0.015 to 4 ,ug/ml; trimethoprim-sulfamethoxazole, 0.5/9.5 to 32/608 ,ug/ mnl; and tetracycline, 0.25 to 16 ,ug/ml.The inoculum was a suspension of the organism in …”
mentioning
confidence: 99%
“…Von Gravenitz (14) reviewed the clinical significance of flavobacteria. Strains of Flavobacterium odoratum isolated from clinical specimens have been shown to be resistant to penicillins, cephalosporins, imipenem, and aztreonam (12).…”
mentioning
confidence: 99%
“…Likewise, carumonam had very limited activity against a much larger spectrum of nonfermenters than suggested by earlier publications (3,4,11,13). Provided that sequential clinical isolates emanating from routine diagnostic testing in a hospital are as resistant to carumonam (MIC5.)…”
mentioning
confidence: 92%